Effectiveness of nanofluid on improving the performance of microchannel heat sink - Wu, Junmei; Zhao, Jiyun; Lei, Jiang; Liu, Bo (Applied thermal engineering, 2016)
•The effectiveness of nanofluid on improving the performance of MCHS is checked.•Al2O3/H2O nanofluid is useful only when the provided pumping power of MCHS is high.•The criteria for suitable nanofluids for MCHSs are proposed. Electronic cooling remains a challenging subject that needs further exploration and research due to its increasing high heat flux. The microchannel is one of several high-heat-flux heat removal designs to meet this requirement. Nanofluids exhibit dramatically enhanced thermal conductivity as well as strong temperature- and size-dependent thermophysical properties, and can be achieved by adding solid particles with diameters below 100 nm in the traditional liquid working fluid. Nanofluids are expected to be utilized in microchannel heat sinks as coolants to gain double profits in heat transfer enhancement to meet the increasing cooling requirements of electronic devices. Does the microchannel heat sink (MCHS) using nanofluid as coolant always provide good cooling to the electronic devices? The answer is No. The aims of the present work are: (1) to provide the criteria for suitable nanofluids for MCHS by checking the effectiveness of Al2O3/H2O nanofluid on improving the overall performance of microchannel heat sink; (2) to answer if/when Al2O3/H2O nanofluid is suitable for MCHS.